2003
DOI: 10.1111/1467-9280.01416
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Attention to Word Content Versus Emotional Tone

Abstract: A Stroop interference task was used to test the hypothesis that people in different cultures are differentially attuned to verbal content vis-à-vis vocal tone in comprehending emotional words. In Study 1, Americans showed greater difficulty ignoring verbal content than ignoring vocal tone (which reveals an attentional bias for verbal content); but Japanese showed greater difficulty ignoring vocal tone than ignoring verbal content (which reveals a bias for vocal tone). In Study 2, Tagalog-English bilinguals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
154
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(171 citation statements)
references
References 18 publications
14
154
1
2
Order By: Relevance
“…The Americans' increased object-based processing is consistent with the finding that Americans attend to individual objects more than do East Asians (Ishii et al, 2003;Kitayama et al, 2003;Masuda & Nisbett, 2001;Nisbett et al, 2001;Nisbett & Masuda, 2003). Areas activated more by Americans when complex scenes are processed include the left middle temporal gyrus (BA 20/21), an area involved in retrieval of semantic knowledge about objects (Cabeza & Nyberg, 2000;Devlin et al, 2002;Martin et al, 1996).…”
Section: Discussionsupporting
confidence: 76%
“…The Americans' increased object-based processing is consistent with the finding that Americans attend to individual objects more than do East Asians (Ishii et al, 2003;Kitayama et al, 2003;Masuda & Nisbett, 2001;Nisbett et al, 2001;Nisbett & Masuda, 2003). Areas activated more by Americans when complex scenes are processed include the left middle temporal gyrus (BA 20/21), an area involved in retrieval of semantic knowledge about objects (Cabeza & Nyberg, 2000;Devlin et al, 2002;Martin et al, 1996).…”
Section: Discussionsupporting
confidence: 76%
“…For instance, Ji et al (2004) found Chinese participants were more relational in reasoning style than European Americans regardless of which languages the participants used in the task. Ishii et al (2003) also found that bilingual Philippines had more attentional biases to verbal tone than to verbal content no matter what language (Taglog or English) the participants used in the study. Based on the findings from the above two studies, cultural factors, but not linguistic factors, appear to have a stronger impact on cognitive processes.…”
Section: Discussionmentioning
confidence: 83%
“…Although there is evidence that environmental affordances make a contribution to the cultural differences in attention that we have found, we do not believe this is the whole story. There are many studies showing greater attention to context by Asians, not only in other attention domains (Ishii, Reyes, & Kitayama, 2003), but also in memory (Hedden et al, 2000;Liu & Nisbett, 2005;Masuda & Nisbett, 2001) and even inference processes, including causal reasoning (Choi, Nisbett, & Norenzayan, 1999;Masuda & Kitayama, 2004;Miyamoto & Kitayama, 2002;Morris & Peng, 1994;Norenzayan & Nisbett, 2000). Thus, although it is likely that ecological factors play a role in attentional differences, the fact that parents socialize different patterns of attention and the fact that cultural differences are found for a wide variety of attention and reasoning tasks indicate that environmental affordances should not be regarded as the sole cause of the effects we have reported.…”
Section: Reasoning Style Visual Experience and Attentionmentioning
confidence: 99%